2018
DOI: 10.1186/s12943-018-0909-7
|View full text |Cite
|
Sign up to set email alerts
|

CircSLC3A2 functions as an oncogenic factor in hepatocellular carcinoma by sponging miR-490-3p and regulating PPM1F expression

Abstract: BackgroundNon-coding RNAs (ncRNAs) have been reported to participate in tumor progression by regulating gene expression. Previous studies showed that protein phosphatase Mg2+/Mn2+ dependent 1F (PPM1F) acts a dual role in cancer growth and metastasis. But, the underlying mechanisms by which ncRNAs regulate PPM1F expression in hepatocellular carcinoma (HCC) are poorly understood.MethodsThe association between PPM1F or miR-490-3p expression and clinicopathological features and prognosis in patients with HCC was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 32 publications
1
64
0
Order By: Relevance
“…Meanwhile, parental genes may also be involved in circRNA biosynthesis 40 . PPM1F has been reported to regulate cancer cell growth and metastasis 41 , whereas its roles in the pathogenesis of T1DM and M1 macrophage activation remain unclear. Notably, our findings provide evidence supporting the hypothesis that circPPM1F-mediated M1 macrophage activation may be attributable to reduced protein levels of the PPM1F gene.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, parental genes may also be involved in circRNA biosynthesis 40 . PPM1F has been reported to regulate cancer cell growth and metastasis 41 , whereas its roles in the pathogenesis of T1DM and M1 macrophage activation remain unclear. Notably, our findings provide evidence supporting the hypothesis that circPPM1F-mediated M1 macrophage activation may be attributable to reduced protein levels of the PPM1F gene.…”
Section: Discussionmentioning
confidence: 99%
“… 1 The understanding of the pathogenesis of colorectal cancer has improved with advances made in the discovery of new oncogenes and anti-oncogenes. 18 - 20 Despite these advances, the underlying mechanism of these diseases remains largely unknown. Recent evidence has shown that snoRNAs play an important regulatory role in the occurrence and development of various diseases, especially cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA TP73-AS1 suppresses triple-negative BC cell vasculogenic mimicry by targeting the miR-490-3p/TWIST1 axis (14). CircSLC3A2 functions as an oncogenic factor in hepatocellular carcinoma by sponging miR-490-3p and regulating PPM1F expression (15). However, the role of miR-490-3p has rarely been studied.…”
Section: Discussionmentioning
confidence: 99%